PENGARUH SUMBER-SUMBER PENDAPATAN ASLI DAERAH TERHADAP BELANJA DAERAH DI KABUPATEN BUNGO - Perdana, Afdhal Chatra (Jurnal Benefita, 2017)
Indonesian government policy on regional autonomy, which began to be implemented effective on January 1, 2001 since the promulgation of Law No. 22 of 1999 which last revised by Act number 23 of 2014, a policy that is seen as a democratic and fulfilling aspects of decentralization of government real , Decentralization alone has the objective to improve the welfare and service to the community, the development of democratic life, justice, equity, and the maintenance of harmonious relations between the center and regions as well as between daerah. This study aims to examine the Original Regional Revenue on Regional Expenditure in Bungo District Year 2006-2014. The result of the research shows that there is a positive and significant influence between the sources of Local Original Income (X1, X2, X3, X4) on local expenditure (Y) in Bungo District. The amount of influence simultaneously between sources of Original Revenue (X1, X2, X3, X4) to local expenditure (Y) in Bungo District is shown with the value of R2 is 99.40%.